2021
DOI: 10.1002/cpt.2316
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Bleeding and Thromboembolic Events in Direct Oral Anticoagulant Users

Abstract: This study aimed to analyze associations between genetic variants and the occurrence of clinical outcomes in dabigatran, apixaban, and rivaroxaban users. This was a retrospective real-world study linking genotype data of three Finnish biobanks with national register data on drug dispensations and healthcare encounters. We investigated several single-nucleotide variants (SNVs) in the ABCG2, ABCB1, CES1, and CYP3A5 genes potentially associated with bleeding or thromboembolic events in direct oral anticoagulant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 43 publications
3
42
4
2
Order By: Relevance
“…Pharmacogenomic studies on rivaroxaban mainly focus on single nucleotide polymorphisms (SNPs) of CYP3A4 / 5 and ABCB1 genes. It has been reported that ABCB1 polymorphisms or haplotypes are correlated with peak concentration of rivaroxaban in a steady‐state, 11 and have been associated with rivaroxaban‐induced thrombotic events 12 . However, genetic basis of rivaroxaban‐induced bleeding events has not been fully addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacogenomic studies on rivaroxaban mainly focus on single nucleotide polymorphisms (SNPs) of CYP3A4 / 5 and ABCB1 genes. It has been reported that ABCB1 polymorphisms or haplotypes are correlated with peak concentration of rivaroxaban in a steady‐state, 11 and have been associated with rivaroxaban‐induced thrombotic events 12 . However, genetic basis of rivaroxaban‐induced bleeding events has not been fully addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, this study suggests that the pharmacogenetic approach to DOACs is a relatively new field of research and that all observations made so far need further consideration and the execution of additional and larger replication studies. In this regard, a recent retrospective study performed on 1806 patients treated with dabigatran, rivaroxaban, or apixaban has identified and confirmed a close correlation between ABCB1 single nucleotide variants and haplotypes with clinical outcomes in rivaroxaban and apixaban users [13]. Similarly, other recent studies have confirmed the correlation between ABCB1 and CES1 SNPs and plasma levels of dabigatran in Chinese patient populations [14].…”
mentioning
confidence: 75%
“…ABCB1 variants are potential factors affecting thromboembolic events in dabigatran users and bleeding events 18 . Earlier studies have found associations between genetic variability and plasma levels of direct oral anticoagulants 19,20 . ABCB1 SNP 1045642 is associated with a reduced risk for thromboembolic outcomes, while rs4148738 is associated with a lower risk for bleeding events in apixaban users.…”
Section: Discussionmentioning
confidence: 97%